Early-life peripheral infections reprogram retinal microglia and aggravate neovascular age-related macular degeneration in later life - Masayuki Hata; Maki Hata; Elisabeth M.M.A. Andriessen; Rachel Juneau; Frédérique Pilon; Sergio Crespo-Garcia; Roberto Diaz-Marin; Vera Guber; Francois Binet; Frédérik Fournier; Manuel Buscarlet; Caroline Grou; et al. (The Journal of Clinical Investigation, 2023)
Pathological neovascularization in age-related macular degeneration (nvAMD) drives the principal cause of blindness in the elderly. While there is a robust genetic association between genes of innate immunity and AMD, genome-to-phenome relationships are low, suggesting a critical contribution of environmental triggers of disease. Possible insight comes from the observation that a past history of infection with pathogens such as Chlamydia pneumoniae, or other systemic inflammation, can predispose to nvAMD in later life. Using a mouse model of nvAMD with prior C. pneumoniae infection, endotoxin exposure, and genetic ablation of distinct immune cell populations, we demonstrated that peripheral infections elicited epigenetic reprogramming that led to a persistent memory state in retinal CX3CR1+ mononuclear phagocytes (MNPs). The immune imprinting persisted long after the initial inflammation had subsided and ultimately exacerbated choroidal neovascularization in a model of nvAMD. Single-cell assay for transposase-accessible chromatin sequencing (scATAC-seq) identified activating transcription factor 3 (ATF3) as a central mediator of retina-resident MNP reprogramming following peripheral inflammation. ATF3 polarized MNPs toward a reparative phenotype biased toward production of proangiogenic factors in response to subsequent injury. Therefore, a past history of bacterial endotoxin–induced inflammation can lead to immunological reprograming within CNS-resident MNPs and aggravate pathological angiogenesis in the aging retina.